2016
DOI: 10.1073/pnas.1524187113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serotonin 2A/1A receptor stimulation on social exclusion processing

Abstract: Social ties are crucial for physical and mental health. However, psychiatric patients frequently encounter social rejection. Moreover, an increased reactivity to social exclusion influences the development, progression, and treatment of various psychiatric disorders. Nevertheless, the neuromodulatory substrates of rejection experiences are largely unknown. The preferential serotonin (5-HT) 2A/1A receptor agonist, psilocybin (Psi), reduces the processing of negative stimuli, but whether 5-HT2A/1A receptor stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 76 publications
(101 reference statements)
3
110
3
3
Order By: Relevance
“…The possibility that our manipulation did not work is further weakened by the fact that, in past research, Cyberball was effective in affecting self-reported perceptions of social exclusion (Van Beest, Williams, & Van Dijk, 2011;Walasek et al, 2015;Williams & Jarvis, 2006;Zadro et al, 2004) and had an impact on relevant brain activity (Eisenberger, Lieberman, & Williams, 2003;Preller et al, 2016) and behaviours (Lustenberger & Jagacinski, 2010;Warburton, Williams, & Cairns, 2006). In our studies, despite the significant and robust effect of a lowered need for belonging, we observed no differences in performance in the judgement and decision-making tasks.…”
Section: All Alone But Not Bad Decision-makerscontrasting
confidence: 66%
“…The possibility that our manipulation did not work is further weakened by the fact that, in past research, Cyberball was effective in affecting self-reported perceptions of social exclusion (Van Beest, Williams, & Van Dijk, 2011;Walasek et al, 2015;Williams & Jarvis, 2006;Zadro et al, 2004) and had an impact on relevant brain activity (Eisenberger, Lieberman, & Williams, 2003;Preller et al, 2016) and behaviours (Lustenberger & Jagacinski, 2010;Warburton, Williams, & Cairns, 2006). In our studies, despite the significant and robust effect of a lowered need for belonging, we observed no differences in performance in the judgement and decision-making tasks.…”
Section: All Alone But Not Bad Decision-makerscontrasting
confidence: 66%
“…Recent studies have also examined mystical-type (Barrett, Johnson, & Griffiths, 2015; Griffiths, Richards, McCann, & Jesse, 2006; Griffiths et al, 2011) or spiritual (Kometer, Pokorny, Seifritz, & Volleinweider, 2015) experiences, changes in self-referential processing or “ego dissolution” (Carhart-Harris et al, 2014; Tagliazucchi et al, 2016), altered social processing (Preller et al, 2016), visual imagery (Kaelen et al, 2016), changes in emotional experience (Kaelen et al, 2015; Kraehenmann et al, 2015), personality change (Carhart-Harris, Kaelen et al, 2016; Lebedev et al, 2016; MacLean, Johnson, & Griffiths, 2011), positive mental health outcomes (Hendricks, Thorne, Clark, Coombs, & Johnson, 2015; Johansen & Krebs, 2015), and enduring positive changes in attitudes, mood and behavior (Griffiths, Richards, Johnson, McCann, & Jesse, 2008; Griffiths et al, 2011) occasioned by these compounds. However, both recent experimental reports (Griffiths et al, 2006; Griffiths et al, 2011; Johnson et al, 2014; Studerus, Kometer, Hasler, & Vollenweider, 2011) and past clinical reports (Cohen, 1960; Strassman, 1984) indicate that challenging psychological experiences during the acute effects of psychedelics are not uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…Three publications were duplicates, meaning data from the same experiment was reported (see Table 1). While one duplicate reported identical data [20], two duplicates differed in sample size [21,22]. Based on requests to the authors, we included the bigger samples [23,24].…”
Section: Included Datamentioning
confidence: 99%